Pengaruh Pajak, Kepemilikan Asing Terhadap Keputusan Transfer Pricing - Yohana Sugianti Nasrin (Jurnal Mutiara Ilmu Akuntansi, 2023)
This study aims to analyze the effect of tax and foreign ownership on the company’s transfer pricing decisions. The population in this study were 80 manufacturing companies in the Basic Industry and Chemical sectors which were listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The sampling method used purposive sampling method. The data used is secondary data using panel data regression analysis using eviews 9.0 software. The results of the study show that the tax variable has no significant effect on transfer pricing decisions, foreign ownership variables have no effect on transfer pricing decisions, but simultaneously or together taxes and foreign ownership have a positive and significant effect on transfer pricing decisions.